Hydrophilic Modification of PVDF Microfiltration Membrane with Poly (Ethylene Glycol) Dimethacrylate through Surface Polymerization. Issue 2 (22nd January 2018) - Chen, Gui-E; Sun, Wei-Guang; Kong, Ya-Fang; Wu, Qiong; Sun, Li; Yu, Jun; Xu, Zhen-Liang
ABSTRACT: The hydrophilic modification of poly (vinylidene fluoride) (PVDF) membrane with poly (ethylene glycol) dimethacrylate (PEGDMA) through grafting reaction for antifouling was reported. The influence of PEGDMA content, reaction temperature and time, on the structure, morphology, antifouling, and hydrophilicity of PVDF-g-PEGDMA membrane has been investigated. The PEGDMA monomers that were grafted on the surface of PVDF microfiltration membrane were confirmed by Attenuation total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and X-ray photoelectron spectroscopy (XPS), and morphology study conducted by SEM revealed the changes before and after modification. The protein adsorption, filtration performance, water content, and dynamic contact angle were used to characterize the antifouling and hydrophilicity of the modified PVDF membranes. Compared with the pristine PVDF membrane, the bovine serum albumin (BSA) adsorption on the PVDF-g-PEGDMA membrane decreased about 80%, and the water contact angle of the membrane dropped to 0°. Besides, the experimental results revealed no significant differences between the membrane samples with respect to pore size. GRAPHICAL ABSTRACT: